Characterization of Sus scrofa small non-coding RNAs present in both female and male gonads. - Dorota Kowalczykiewicz; Aleksandra Świercz; Luiza Handschuh; Katarzyna Leśniak; Marek Figlerowicz; Jan Wrzesinski (PLoS ONE)
Small non-coding RNAs (sncRNAs) are indispensable for proper germ cell development, emphasizing the need for greater elucidation of the mechanisms of germline development and regulation of this process by sncRNAs. We used deep sequencing to characterize three families of small non-coding RNAs (piRNAs, miRNAs, and tRFs) present in Sus scrofa gonads and focused on the small RNA fraction present in both male and female gonads. Although similar numbers of reads were obtained from both types of gonads, the number of unique RNA sequences in the ovaries was several times lower. Of the sequences detected in the testes, 2.6% of piRNAs, 9% of miRNAs, and 10% of tRFs were also present in the ovaries. Notably, the majority of the shared piRNAs mapped to ribosomal RNAs and were derived from clustered loci. In addition, the most abundant miRNAs present in the ovaries and testes are conserved and are involved in many biological processes such as the regulation of homeobox genes, the control of cell proliferation, and carcinogenesis. Unexpectedly, we detected a novel sncRNA type, the tRFs, which are 30-36-nt RNA fragments derived from tRNA molecules, in gonads. Analysis of S. scrofa piRNAs show that testes specific piRNAs are biased for 5' uracil but both testes and ovaries specific piRNAs are not biased for adenine at the 10th nucleotide position. These observations indicate that adult porcine piRNAs are predominantly produced by a primary processing pathway or other mechanisms and secondary piRNAs generated by ping-pong mechanism are absent.